Sustainable Economic Development: Study on the Ujung Kulon Geopark - Rani Meida; Adinda Sri Maryam; Ima Amaliah (Budapest International Research and Critics University, 2022)
Geopark development is one sector that can support economic shifts that have added value and are protective to ensure sustainability. In this study, the Ujung Kulon geopark is one of the appropriate Geoparks to be studied and analyzed how the planning for the development of this geopark can provide benefits for sustainable economic development. The research method used in this research is qualitative which is elaborated by descriptive analysis using the SWOT analysis technique. From the results of the analysis, the Ujung Kulon Geopark has added value. It has various world heritages which are also protected by the United Nations Educational, Scientific and Cultural Organization because its area includes a very wide protected forest and is also the last habitat of the one-horned rhino. This geopark also has the opportunity to develop well because it has government support so that its management is legally valid. However, the weakness of this geopark is the incomplete public facilities for tourists and the threat of natural disasters such as tsunamis and droughts. Therefore, the government must have careful planning so that the development of this geopark can contribute economically. In conclusion, to be able to support sustainable economic development from this geopark development plan, it is necessary to develop economics through investment, agriculture, and environmental policies. Therefore, to build integrated tourism, it is necessary to pay more attention to product and service development, national branding, SME development, protection of natural and socio-cultural resources, and analysis of tourism supply and demand.